Nuclear microRNA-466c regulates Vegfa expression in response to hypoxia - Laitinen, P; Väänänen, M-A; Kolari, I-L; Mäkinen, PI; Kaikkonen, MU; Weinberg, MS; Morris, KV; Korhonen, P; Malm, T; Ylä-Herttuala, S; Roberts, TC; Turunen, MP; et al. (Public Library of Science, 2022)
MicroRNAs are well characterized in their role in silencing gene expression by targeting 3´-UTR of mRNAs in cytoplasm. However, recent studies have shown that miRNAs have a role in the regulation of genes in the nucleus, where they are abundantly located. We show here that in mouse endothelial cell line (C166), nuclear microRNA miR-466c participates in the regulation of vascular endothelial growth factor a (Vegfa) gene expression in hypoxia. Upregulation of Vegfa expression in response to hypoxia was significantly compromised after removal of miR-466c with CRISPR-Cas9 genomic deletion. We identified a promoter-associated long non-coding RNA on mouse Vegfa promoter and show that miR-466c directly binds to this transcript to modulate Vegfa expression. Collectively, these observations suggest that miR-466c regulates Vegfa gene transcription in the nucleus by targeting the promoter, and expands on our understanding of the role of miRNAs well beyond their canonical role.